2014
DOI: 10.1136/annrheumdis-2014-205372
|View full text |Cite
|
Sign up to set email alerts
|

The outcomes of juvenile idiopathic arthritis in children managed with contemporary treatments: results from the ReACCh-Out cohort

Abstract: Most children with JIA managed with contemporary treatments attain inactive disease within 2 years of diagnosis and many are able to discontinue treatment. The probability of attaining remission within 5 years of diagnosis is about 50%, except for children with polyarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
173
2
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 211 publications
(198 citation statements)
references
References 24 publications
16
173
2
7
Order By: Relevance
“…The result is that clinical outcome has improved and complete disease control can often be achieved 1 .…”
mentioning
confidence: 98%
“…The result is that clinical outcome has improved and complete disease control can often be achieved 1 .…”
mentioning
confidence: 98%
“…These drugs decrease pain by analgesic effect at low doses, but have antiinflammatory effect at higher doses. In the first 1-3 days of treatment, a response in the form of decreased pain is obtained (1)(2)(3)11).…”
Section: Non-biological Drugs Used In Treatment Of Juvenile Idiopathimentioning
confidence: 99%
“…In addition, the patient's preference should be considered in terms of the mode of administration and frequency of administration. The limitations for use of these drugs include inadequate long-term safety data and cost, though they are efficient drugs (1)(2)(3)(11)(12)(13)(14).…”
Section: Biological Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Canadian researchers have demonstrated that patients with JIA (except rheumatoid factor-positive polyarticular JIA) have a 70-90% chance of attaining inactive disease by 2 years postdiagnosis 2 . Inactive disease was defined using modified Wallace criteria 3 .…”
Section: Participation In Leisure Activities Among Canadian Children mentioning
confidence: 99%